Trzy koncepcje dyskursu: Foucault, Laclau, Habermas - Rasiński, Lotar (Kultura-Społeczeństwo-Edukacja, 2019)
The aim of this article is to examine three currently dominant concepts of discourse, developed by Michel Foucault, Ernesto Laclau and Jürgen Habermas. I argue that these concepts of discourse constitute neither a coherent methodological agenda nor a coherent theoretical vision. That means that the reference to discourse will always imply engaging with a particular theoretical framework. I briefly discuss the theoretical traditions from which these concepts emerged and point to the essential elements which the respective concepts of discourse derived from these traditions. Concluding, I examine differences between and similarities in the discussed concepts, whereby I address, in particular, the relationship between discourse and everyday language, the notion of subjectivity and the concept of the social world.